Combining Ability and Heterosis for Market Yield in Green Asparagus - Amato, Lucía Dolores (2022)
In asparagus, current cultivars are mostly hybrids (known as clonal hybrids) derived from crosses between two parents, female and male, with good combining ability. Despite the fact that clonal hybrids have been obtained for more than 40 years, studies of the heterosis and combining abilities involved are limited. Similarly, there are no published studies regarding the association between genetic divergence and heterosis. In this sense, we evaluated two sets of diallel crosses including 12 accessions from 11 different origins for marketable green asparagus production. Parentals were also included as a way to assess heterosis. The variation for market yield was highly significant for both sets. Best parent heterosis was over 100% in four cases. The best experimental hybrid did not significant differ from the Atticus F1 all-male check. The general combining ability (GCA) and specific combining ability (SCA) were significant, with a relative greater contribution of the SCA than the GCA to the variation among crosses. The association between genetic distances and heterosis failed to be significant. The best experimental hybrids were obtained when UC157 and KBF (origins from the USA and the UK) were crossed to Argenteuil, Limburgia and Esparrago de Navarra (origins from France, the Netherlands and Spain).